2019
DOI: 10.4110/in.2019.19.e7
|View full text |Cite
|
Sign up to set email alerts
|

Aged Sanroque Mice Spontaneously Develop Sjögren's Syndrome-like Disease

Abstract: Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disorder that affects mainly salivary and lacrimal glands, but its cause remains largely unknown. Clinical data indicating that SS occurs in a substantial proportion of patients with lupus points to common pathogenic mechanisms underlying the two diseases. To address this idea, we asked whether SS develops in the lupus-prone mouse strain sanroque (SAN). Owing to hyper-activation of follicular helper T (Tfh) cells, female SAN mice developed lupus-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Also, a subsequent study has shown that sanroque mice develop systemic autoimmunity in a manner partly dependent on Bcl6, which is a master regulator critical for Tfh cells and germinal center formation [58]. Sanroque mice also develop other autoimmune symptoms including Sj€ ogren's syndrome-like symptoms as they age [59].…”
Section: Roquin-12mentioning
confidence: 99%
“…Also, a subsequent study has shown that sanroque mice develop systemic autoimmunity in a manner partly dependent on Bcl6, which is a master regulator critical for Tfh cells and germinal center formation [58]. Sanroque mice also develop other autoimmune symptoms including Sj€ ogren's syndrome-like symptoms as they age [59].…”
Section: Roquin-12mentioning
confidence: 99%
“…Joint-draining (axillary and inguinal) and cervical lymph node (cLN) cells from SKG mice were analyzed by FACS, as previously described (19). Anti-CD4-PerCP, anti-IFNγ-FITC, and anti-IL-17A-PE were purchased from BD Biosciences (San Jose, CA, USA) or eBioscience (San Diego, CA, USA).…”
Section: Facs Analysismentioning
confidence: 99%
“…Submandibular salivary glands were removed post mortem from SKG mice that had been injected with curdlan or PBS 8-10 weeks previously. Paraffin-embedded tissue sections were prepared and stained with H&E as described (19). In some experiments, tissue sections were stained with anti-CD45 IgG (Leica Biosystems, Newcastle, UK) or with anti-mouse IgG-biotin (Sigma-Aldrich), and examined by standard immunohistochemical methods, as described (19).…”
Section: Histopathologic Examinationmentioning
confidence: 99%
See 2 more Smart Citations